RBM20, a Therapeutic Target to Alleviate Myocardial Stiffness via Titin Isoforms Switching in HFpEF - Li, Na; Hang, Weijian; Shu, Hongyang; Zhou, Ning (Frontiers in Cardiovascular Medicine, 2022)
Increased myocardial stiffness is critically involved in heart diseases with impaired cardiac compliance, especially heart failure with preserved ejection fraction (HFpEF). Myocardial stiffness mainly derives from cardiomyocyte- and extracellular matrix (ECM)-derived passive stiffness. Titin, a major component of sarcomeres, participates in myocardial passive stiffness and stress-sensitive signaling. The ratio of two titin isoforms, N2BA to N2B, was validated to influence diastolic dysfunction via several pathways. RNA binding motif protein 20 (RBM20) is a well-studied splicing factor of titin, functional deficiency of RBM20 in mice profile improved cardiac compliance and function, which indicated that RBM20 functions as a potential therapeutic target for mitigating myocardial stiffness by modulating titin isoforms. This minor review summarized how RBM20 and other splicing factors modify the titin isoforms ratio, therefore providing a promising target for improving the myocardial compliance of HFpEF.